Production of Job Mix Design FC 25 SF (Silica Fume) with SFRC (Steel Fiber Reinforcement Concrete) - J Januarto; S Syawal; F Fauzan; Herlina Suciati (CV. Media Digital Publikasi Indonesia, 2025)
When building anything, concrete is a must-have ingredient. There has been a recent uptick in studies examining the tensile strength of concrete. In order to make concrete more resistant to tensile pressures generated by temperature and weather fluctuations encountered by expansive surfaces, steel fiber concrete is being developed. Adding steel fiber to concrete is one way to boost its tensile strength. When used in conjunction with steel fiber, silica fume is an additive that may seal and compress the concrete surface. Adding silica fume to concrete improves its quality and makes it weatherproof. This research aims to enhance the compressive strength of concrete by using steel fiber and silica fume. Some of the ingredients needed to make concrete include steel fiber and silica fume. At 7,14, and 28 days of curing time, cylinders measuring 15 x 30 cm were used in the investigation. Methods and procedures based on concrete standard test and SNI 03-2834-2000 were used to perform in this study at the PT. Remicon Widyaprima Laboratory. A projected concrete compressive strength of 25 MPa was determined by the study's findings. After 28 days, the concrete with the maximum compressive strength was 28.30 MPa, achieved by a combination of steel fiber and silica fume, according to the findings of this research. In comparison, regular concrete had a compressive strength of around 26.25 MPa.